Site‐Engineered Tetragonal ZrO2 Nanoparticles: A Promising Oxygen Reduction Catalyst with High Activity and Chemical Stability in Alkaline Medium. Issue 6 (20th January 2022) - Veettil, Vineesh Thazhe; Mohankumar, Meera; Zitoun, David
Abstract: Practical implementation of anion exchange membrane fuel cells mainly relies on the choice of highly active and stable oxygen reduction reaction (ORR) catalysts. Transition metal oxides based on Group 4 and 5 are well known for their chemical stability and corrosion‐resistance and they are earth‐abundant too. Among them, zirconia (ZrO2 ) has exceptional chemical stability, but its poor conductivity and less active sites hinder the application of zirconia‐based materials toward ORR. In order to bring out the best activity from ZrO2, careful site engineering without losing the phase purity and chemical stability is essential. In this context, nitrogen doping on tetragonal zirconia (t‐ZrO2 ) as a viable method to obtain a highly active ORR catalyst is adopted. The temperature for the phase pure synthesis of t‐ZrO2 is optimized by crystallographic study. The nitrogen doping in the zirconia lattice is confirmed by various microscopy and spectroscopy analysis. The N doped tetragonal zirconia nanoparticles on N doped carbon (N:ZrO2 –NC) show much improved ORR activity than pristine zirconia counterparts in terms of onset potential, current density, and 4e _ selectivity in alkaline medium. The ORR activity of N:ZrO2 ‐NC is approaching the one of Pt/C with excellent chemical and electrochemical stability. Abstract : Augmented oxygen reduction reaction performance of site‐engineered tetragonal ZrO2 nanoparticles is reported.